Sharia hotel preferences among tourists in Bogor City: Factors and insights - Luthfiana, Alda; Wiliasih, Ranti; Irfany, Mohammad Iqbal; Haq, Daffa Aqomal (Journal of Sustainable Tourism and Entrepreneurship, 2022)
Purpose: The objective of this study is to examine the factors influencing consumer demand for Sharia hotel services in Bogor City and their characteristics to provide invaluable guidance for related parties. Research Methodology:  This study employs descriptive and multiple regression analyses using data collected from Sharia hotel consumers in Bogor City using a convenience sampling technique with 59 samples. Results: The results show that consumers of Sharia hotels in Bogor City use conventional hotel services more often than Sharia hotels. The factors influencing tourists’ use of Sharia hotel services in Bogor City are the relative prices of Sharia hotels to conventional hotels, knowledge, religiosity, service quality, and facilities owned by Sharia hotels. Limitations: The study is geographically confined to three specific Sharia hotels in Bogor City: Sahira Hotel, Sahira Butik Hotel Bogor, and Sahira Butik Hotel Pakuan, which may not be representative of sharia hotels in other regions. Contributions: Offers insights into consumer behavior in Bogor City's Sharia hotel sector, aiding future business and policy decisions in halal tourism.